Analisis Model Pembelajaran Picture And Picture Pada Pembelajaran Ski Di MTs Negeri 2 Kepahiang - Eka Yanuarti; Cintia Nur Jannah; Melisa Eka Putri; Mesi Sulastri; Nada Magfiroh (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
The research used is a qualitative research and the research approach used is a descriptive approach. The subjects of this study were SKI teachers and students. The types and sources of data used in this research are (1) primary data, related to the initial data. (2) secondary data, related to additional data. Data collection techniques are observation, interviews and documentation. The use of data analysis techniques in the field are: (1) data reduction, (2) data presentation, (3) drawing conclusions and verification. In the data validity technique in this study, the examination was carried out by triangulation. The results showed that: (1) the application of the Picture and Picture learning model to class VIII SKI lessons, namely, the SKI teacher has taken the steps to apply the picture and picture model to class VIII SKI learning in accordance with the existing theory. (2) the supporting and inhibiting factors, namely, the supporting factors for the application of the Picture And Picture learning model include, the availability of picture tools and media in madrasas is actually quite adequate such as infocus and computers, the availability of books in the library is sufficient and on the inhibiting factors it is not found that SKI teachers experience difficulties when dealing with student abilities. SKI teachers also don't seem to have any difficulty in determining pictures that are appropriate to the subject matter.